2015
DOI: 10.3171/2014.11.spine1441
|View full text |Cite
|
Sign up to set email alerts
|

How the neck affects the back: changes in regional cervical sagittal alignment correlate to HRQOL improvement in adult thoracolumbar deformity patients at 2-year follow-up

Abstract: OBJECT Regional cervical sagittal alignment (C2–7 sagittal vertical axis [SVA]) has been shown to correlate with health-related quality of life (HRQOL). The study objective was to examine the relationship between cervical and thoracolumbar alignment parameters with HRQOL among patients with operative and nonoperative adult thoracolumbar deformity. METHODS This is a multicenter prospective data collection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
75
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(75 citation statements)
references
References 17 publications
0
75
0
Order By: Relevance
“…We have not measured the T1-slope in our patients. Nonetheless, the impact of global spine parameters and the T1-slope are still under discussion and are not validated by level 1 studies, although prospective multicenter data already exist [52]. Many factors influence the outcome above all of these parameters [53].…”
Section: Discussionmentioning
confidence: 99%
“…We have not measured the T1-slope in our patients. Nonetheless, the impact of global spine parameters and the T1-slope are still under discussion and are not validated by level 1 studies, although prospective multicenter data already exist [52]. Many factors influence the outcome above all of these parameters [53].…”
Section: Discussionmentioning
confidence: 99%
“…In recent literature, it seems that cervical lordosis restoration has a major impact. Protopsaltis et al have shown that this parameter was directly correlated to the scores of quality of life in adults [17]. A low value of thoracic kyphosis being at the origin of a kyphotic decompensation of the cervical spine is a major element to take into account when correcting this kind of spinal deformity [18].…”
Section: Discussionmentioning
confidence: 99%
“…Most of these studies focus on the importance of the restoration of lumbar lordosis and its relation to the pelvic incidence [8,9,24]. Only recently has the role of cervical sagittal measures in outcomes for spine deformity been studied [12][13][14][15][16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, attention has been directed to the impact of adult scoliosis or scoliosis treatment on the cervical spine [12][13][14][15][16][17][18][19][20]. Several authors have proposed a set of standardized radiographic parameters [21] to help evaluate the cervical spine in patients with adult spinal deformity using full-length 36-inch radiographs.…”
Section: Introductionmentioning
confidence: 99%